2021
DOI: 10.1103/physreve.104.024101
|View full text |Cite
|
Sign up to set email alerts
|

Densest ternary sphere packings

Abstract: We present our exhaustive exploration of the densest ternary sphere packings (DTSPs) for 45 radius ratios and 237 kinds of compositions, which is a packing problem of three kinds of hard spheres with different radii, under periodic boundary conditions by a random structure searching method. To efficiently explore DTSPs we further develop the searching method based on the pilingup and iterative balance methods [Koshoji et al., Phys. Rev. E 103, 023307 (2021)]. The unbiased exploration identifies diverse 38 puta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
82
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(96 citation statements)
references
References 31 publications
13
82
0
1
Order By: Relevance
“…While some studies had discussed the dense ternary sphere packings [11][12][13][14][15], the putative densest ternary sphere packings (DTSPs) had not been predicted until recent years; the densest phase diagrams for the ternary systems had not been constructed. However, we successfully found the 37 putative DTSPs with construction of phase diagrams in 2021 [16]. The result showed that when the radius ratios of small and medium spheres are small, the DTSPs tend to be complex because the spheres comprise clusters in many cases and the clusters are placed in relatively small voids consisting of large spheres.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…While some studies had discussed the dense ternary sphere packings [11][12][13][14][15], the putative densest ternary sphere packings (DTSPs) had not been predicted until recent years; the densest phase diagrams for the ternary systems had not been constructed. However, we successfully found the 37 putative DTSPs with construction of phase diagrams in 2021 [16]. The result showed that when the radius ratios of small and medium spheres are small, the DTSPs tend to be complex because the spheres comprise clusters in many cases and the clusters are placed in relatively small voids consisting of large spheres.…”
Section: Introductionmentioning
confidence: 93%
“…For example, the crystal of the LaH 10 , which is one of the superhydrides synthesized under high pressure, corresponds to the XY 10 structure that is one of the DBSPs. On the other hand, the study [16] indicated that the correspondence of the DTSPs with crystals seems to be exceptional. In fact, for most of DTSPs, it is difficult to understand the structural property from the perspectives of chemical bonds and/or local polyhedrons which are typically found in coordination structures to transition elements.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations